The influence of the surface load exerted by a piezoelectric contact sensor on testing results: I. The displacement field in the solid - Radziszewski, L. (Archives of Acoustics, 2003)
The influence of a strong discontinuity wave on its measurement with a piezoelectric sensor was analysed analytically. The one-dimensional model of the mechanical contact between the ultrasonic sensor and the solid medium was developed. The displacement field was calculated with the d’Alambert’s method. The evaluation was made locally at the front of the distortion. It was found that the relative difference of a displacements between the free and loaded surfaces ranges from 10% to 72% and the mass M has no influence on it in the first time interval. It is affected not only by the wave impedances but also by surfaces of the sensor and sample. After a long period of time (depending on the mass M) the influence of the surface loading becomes much smaller. Part I of the paper contains the discussion of the displacement field in the solid, the electricaltransients generated by the piezoelectic sensor are given in Part II.